56. LAPAROSCOPIC DISTAL GASTRECTOMY WITH D2 LYMPHADENECTOMY AND BILLROTH II RECONSTRUCTION FOR GASTRIC ADENOCARCINOMA (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the technique of laparoscopic distal gastrectomy with D2 lymphadenectomy and Billroth II reconstruction in the treatment of gastric adenocarcinoma, aiming to evaluate the feasibility and safety of the procedure.Methods: A descriptive study was conducted on 90 patients with gastric adenocarcinoma at Nghe An General Friendship Hospital from 2022 to 2024. All patients underwent total laparoscopic surgery, with gastrojejunostomy performed before gastric transection, using linear staplers and left liver suspension technique.Results: All 90 cases successfully completed laparoscopic surgery without conversion to open surgery. The intraoperative complication rate was low (3.3%) and all were managed safely. The mean operative time was 174.4 ± 19.4 minutes. No intraoperative mortality was reported.Conclusion: Laparoscopic distal gastrectomy with D2 lymphadenectomy and Billroth II reconstruction is a safe and feasible technique, suitable for wider application in the treatment of gastric adenocarcinoma.